Quality of life in the older adults: The protective role of self-efficacy in adequate coping in patients with chronic diseases - Cudris-Torres, Lorena; Alpi, Stefano Vinaccia; Barrios-Núñez, Álvaro; Gaviria Arrieta, Natali; Mejía Gutiérrez, Jéssica; Alvis Barranco, Libia; Rios-Carlys, Gerson; Cuenca-Calderón, Silvia E.; Bermúdez, Valmore; Hernández-Lalinde, Juan; Riveira Zuleta, Carlos Arturo; Bahamón, Marly Johana; et al. (Frontiers in Psychology, 2023)
The purpose of the present study was to establish the association between self-efficacy, perception of disease, emotional regulation, and fatigue and the health-related quality of life in older adults living in the departments of Cesar and Atlántico in Colombia and who have been diagnosed with a chronic disease. The participants were 325 older adults of both sexes, with literacy and no presence of cognitive impairment in the Mini-Mental State Examination (MMSE); A non-probabilistic sampling was carried out. We used the MOS-SF-36 questionnaire, the Brief Illness Perception Questionnaire scale for measuring the perception of disease, the Stanford Patient Education Research Center’s Chronic Disease Self self-efficacy questionnaire for chronic patients, the Difficulties in Emotional Regulation Scale, and the Fatigue Severity Questionnaire as measurement instruments. The design was non-experimental cross-sectional with a correlational scope. The results indicate that self-efficacy, disease perception, emotional regulation and severity of fatigue are variables that could impact the physical function of quality of life, confirming that self-efficacy would work as a factor that decreases the probability that a participant score low on this dimension of quality of life. On the other hand, both the perception of the disease and the severity of fatigue were identified as factors that probably negatively influence quality of life.